Actions and mechanisms of polyunsaturated fatty acids on voltage-gated ion channels - Elinder, Fredrik; Liin, Sara I. (Frontiers in Physiology, 2017)
Polyunsaturated fatty acids (PUFAs) act on most ion channels, thereby having significant physiological and pharmacological effects. In this review we summarize data from numerous PUFAs on voltage-gated ion channels containing one or several voltage-sensor domains, such as voltage-gated sodium (NaV), potassium (KV), calcium (CaV), and proton (HV) channels, as well as calcium-activated potassium (KCa), and transient receptor potential (TRP) channels. Some effects of fatty acids appear to be channel specific, whereas others seem to be more general. Common features for the fatty acids to act on the ion channels are at least two double bonds in cis geometry and a charged carboxyl group. In total we identify and label five different sites for the PUFAs. PUFA site 1: The intracellular cavity. Binding of PUFA reduces the current, sometimes as a time-dependent block, inducing an apparent inactivation. PUFA site 2: The extracellular entrance to the pore. Binding leads to a block of the channel. PUFA site 3: The intracellular gate. Binding to this site can bend the gate open and increase the current. PUFA site 4: The interface between the extracellular leaflet of the lipid bilayer and the voltage-sensor domain. Binding to this site leads to an opening of the channel via an electrostatic attraction between the negatively charged PUFA and the positively charged voltage sensor. PUFA site 5: The interface between the extracellular leaflet of the lipid bilayer and the pore domain. Binding to this site affects slow inactivation. This mapping of functional PUFA sites can form the basis for physiological and pharmacological modifications of voltage-gated ion channels.